The Edinburgh companion to First World War periodicals - Demoor, Marysa; Dijck, Cedric van; Van Puymbroeck, Birgit (Edinburgh companions to literature and the humanities., 2023)
The first reference book on First World War newspapers and magazines from the home front to the front lines.